2014
DOI: 10.1364/boe.5.001757
|View full text |Cite
|
Sign up to set email alerts
|

Spectral multiplexing and coherent-state decomposition in Fourier ptychographic imaging

Abstract: Information multiplexing is important for biomedical imaging and chemical sensing. In this paper, we report a microscopy imaging technique, termed state-multiplexed Fourier ptychography (FP), for information multiplexing and coherent-state decomposition. Similar to a typical Fourier ptychographic setting, we use an array of light sources to illuminate the sample from different incident angles and acquire corresponding low-resolution images using a monochromatic camera. In the reported technique, however, multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
113
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(113 citation statements)
references
References 43 publications
0
113
0
Order By: Relevance
“…We note that this basic recovery process assumes the illumination field extending across the sample's lateral extent is coherent. A more advanced FP recovery procedure may incorporate partial coherence modeling [3]. The recovery algorithm starts with a high-resolution spectrum estimate of the sample, 0 ( U x y k , k ) .…”
Section: D Refocusing Via Aperture-scanning Fourier Ptychographymentioning
confidence: 99%
See 3 more Smart Citations
“…We note that this basic recovery process assumes the illumination field extending across the sample's lateral extent is coherent. A more advanced FP recovery procedure may incorporate partial coherence modeling [3]. The recovery algorithm starts with a high-resolution spectrum estimate of the sample, 0 ( U x y k , k ) .…”
Section: D Refocusing Via Aperture-scanning Fourier Ptychographymentioning
confidence: 99%
“…A deconvolution operation can recover the same data that a fully coherent FP setup would capture, assuming the source shape A is known and that noise is negligible. Finally, we note that, a mixed-state formulation can be used to model the partially coherent effects in FP platforms [3]. The finite extent of the light source can be modeled as multiple independent point sources.…”
Section: Appendix A: Partial Coherence Of Aperture-scanning Fourier Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Tian et al [3] demonstrated that it is possible to turn on several LEDs at once during the image collection procedure, showing data reduction from 293 to 40 images, along with a reduction of acquisition time of up to 90%, without significant loss of image fidelity. Multiplexing can also be used for the RGB spectral channels, as shown by Dong et al [12]. These variations on FPM have found applications in quantitative phase imaging [13], gigapixel microscopy [14], high-resolution fluorescence imaging [15] and more [16][17][18].…”
Section: Introductionmentioning
confidence: 99%